Β-N-methylamino-L-alanine Inhibits Human Catalase Activity: Possible Implications for Neurodegenerative Disease Development. (March 2019) - van Onselen, Rianita; Downing, Tim G.
The naturally produced, nonprotein amino acid β- N -methylamino-l -alanine (BMAA) has been proposed as a significant contributor to sporadic neurodegenerative disease development worldwide. However, the existing hypothesized mechanisms of toxicity do not adequately explain the role of BMAA in neurodegenerative disease development. There is evidence for BMAA-induced enzyme inhibition, but the effect of BMAA on human stress response enzymes has received little attention, despite the well-described role of oxidative stress in neurodegenerative disease development. The aim of this study was therefore to investigate the effect of BMAA on human catalase activity and compare it to the known inhibitor 3-amino-1, 2, 4-triazole. BMAA inhibited human erythrocyte catalase in a cell-free exposure to the same extent as the known inhibitor. Based on enzyme kinetics, the inhibition appears to be noncompetitive, possibly as a result of BMAA binding in the nicotinamide adenine dinucleotide phosphate (NADPH) binding site. BMAA-induced catalase inhibition was also observed in a human cell line culture. We therefore propose that BMAA-induced enzyme inhibition, specifically catalase inhibition, is a mechanism of toxicity that may contribute to the neurotoxicity of BMAA, further supporting the role of BMAA in neurodegenerative disease development.